Pemberdayaan Peserta Didik melalui Program Literasi Bahasa Arab di Madrasah Aliyah Mathla’ul Anwar Telukambulu, Batujaya, Karawang - Ilham Fahmi; Muhamad Faizin; Taufik Mustofa; Nur Aini Farida; Saprialman; Nadila (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community engagement program aims to empower students through an Arabic literacy enhancement model implemented at MA Mathla’ul Anwar Telukambulu, Batujaya, Karawang. The main problems identified include low reading comprehension, limited vocabulary mastery, and the absence of sustainable literacy culture among students. The mentoring strategy involved workshops for teachers, development of literacy modules, classroom mentoring, student literacy projects, and creative media integration. The implementation demonstrated significant improvements in students’ reading ability (38%), writing accuracy (41%), and vocabulary acquisition (25–35 new words per student). The program also produced creative outputs such as Arabic literacy corners, vocabulary posters, and student-made Arabic mini anthologies. This study concludes that Arabic literacy-based empowerment contributes effectively to enhancing student competency and fostering a sustainable literacy culture within the madrasah environment.